Effect Of Dolomit CaMg(CO3)2) as Pellet for Intensity of Moulting, Growth and Survival Rate of Shrimp Vanname (Litopenaus vannamei) - sari, Chici Arum; Rusliadi, Rusliadi; Mulyadi, Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on September 2018 until October 2018 at Aquaculture Technology Laboratory of Fisheries and Marine, University Riau, Pekanbaru. The purpose of this experiment was to determine the optimal dose of dolomite CaMg(CO3)2) as pellet for intensity of moulting, growth and survival rate of vanname shrimp (Litopenaus vannamei). The research method use in this study was an experimented method and completely randomized design with five treatments and three replication. The treatments in this study were (P0) control, (P1) 2 mg/ kg, (P2) 3 mg/ kg pakan, (P3) 4 mg/ kg pakan, (P4) 5 mg/ kg. The result shown that adding dolomite at vanname shrimp’s feed of 3 mg/kg (P2) treatment of the best, especially moulting 132 ind, absolute growth weight 0,72 g, daily growth rate 1,57% and survival rate 95%. Water quality range at all treatments were the temperature range was from 28 to 310C, pH ranges was from 5 to 7, dissolved oxygen was from 4,1 to 6,2 mg/L, salinity was from 16 to 18 ppt and ammonia was around 0,00001-0,0053 mg//L.Keywords: Dolomite, moulting, Vanname shrimp.